How the development of chronic morbidity and multimorbidity depends on natural age of menopause: Results from nationally representative cross-sectional Indian study - Pritam Halder; Shubham Kansal; Kartik Chadhar; Aswani Seth; Semanti Das; Saumyarup Pal; Anamika Das; Dheenadhayalan Vijayakumar (Journal of Family Medicine and Primary Care)
Background: Multimorbidity development is linked with the age at menopause. Fewer studies are available to support the findings. This study was conducted to find, how multimorbidity is associated with the natural age of menopause. Methodology: LASI-1, a longitudinal study, collected detailed information on the psychological, social, economic, and health aspects of aging in India. Wave-1 data collection was done in all 35 states and union territories in India. Baseline data was collected from year 2017–2019. As the current study was a secondary data analysis to find the association between multimorbidity and age of menopause, only eligible women’s relevant data was analyzed. Results: A total of 25,256 women were analyzed, 67.8% of participants had at least one comorbidity. The mean age was 58.5 ± 10.17 years. 57.04% and 13.45% women had optimal or suboptimal menopause, while 7.4%, 17.5%, and 4.4% had premature, early, and delayed menopause. A significant association was found for the presence of multimorbidity and premature (AOR 1.19 (1.07–1.32)), early menopause (AOR 1.18 (1.10–1.27)), and optimal age of menopause (AOR 0.83 (0.78–0.88)). Conclusion: There is a high burden of multimorbidity and it is associated with the natural age of menopause. This study would be helpful for effective policymaking and a better primary healthcare approach to deal with the condition.